Beyond brain injury biomarkers: chemoattractants and circulating progenitor cells as biomarkers of endogenous rehabilitation effort in preterm neonates with encephalopathy - Efstathiou, N.; Soubasi, V.; Koliakos, G.; Kantziou, K.; Kyriazis, G.; Slavakis, A.; Dermentzoglou, V.; Michalettou, I.; Drosou-Agakidou, V. (Frontiers in Pediatrics, 2023)
Introduction:Preclinical work and studies in adults have shown that endogenous regeneration efforts that involve mobilization of progenitor cells take place after brain injury. However, kinetics of endogenous circulating progenitor cells(CPCs) in preterm neonates is not well described, particularly their possible role regarding brain injury and regeneration. We aimed to assess the kinetics of CPCs in neonates with encephalopathy of prematurity in relation to brain injury biomarkers, chemoattractants and relevant antenatal and postanal clinical factors, in an effort to outline the related pathophysiology. Materials and methods:47 preterm neonates (of 28-33w GA) were enrolled:31 newborns with no or minimal brain injury(grade I IVH) and 16 prematures with encephalopathy (grade III/IV IVH, PVL or infarct). Peripheral blood samples obtained on days 1, 3, 9, 18 and 45 after birth were analyzed using flow cytometry, focusing on EPCs(early and late Endothelial Progenitor Cells), HSCs(Hematopoietic Stem Cells) and VSELs(Very Small Embryonic-Like Stem Cells). At the same time-points serum levels of S100B, Neuron-specific Enolase(NSE), Erythropoietin(EPO), Insulin-like growth factor‐1(IGF‐1) and SDF-1 were also measured. Neonates were assessed postnatally with brain MRI, and with Bayley III developmental test at 2 years of corrected age. Results:Preterms with brain injury proved to have significant increase of S100B and NSE, followed by increase of EPO and enhanced mobilization mainly of HSCs, eEPCs and lEPCs. IGF-1 was rather decreased in this group of neonates. IGF-1 and most CPCs were intense decreased in cases of antenatal or postnatal inflammation.S100B and NSE correlated with neuroimaging and language scale in Bayley III test, providing good prognostic ability. ` Conclusion:The observed pattern of CPCs’ mobilization and its association with neurotrophic factors following preterm brain injury indicate the existence of an endogenous brain regeneration process. Kinetics of different biomarkers and associations with clinical factors contribute to the understanding of the related pathophysiology and might help to early discriminate neonates with adverse outcome. Timely appropriate enhancement of the endogenous regeneration effort, when it is suppressed and insufficient, using neurotrophic factors and exogenous progenitor cells might be a powerful therapeutic strategy in the future to restore brain damage and improve the neurodevelopmental outcome in premature infants with brain injury.